Intrahepatic and hilar mass-forming cholangiocarcinoma: Qualitative and quantitative evaluation with diffusion-weighted MR imaging. Issue 8 (August 2015) - Fattach, Hassan El; Dohan, Anthony; Guerrache, Youcef; Dautry, Raphael; Boudiaf, Mourad; Hoeffel, Christine; Soyer, Philippe
Highlights: DW-MR imaging helps depicts all intrahepatic or hilar mass-forming cholangiocarcinomas. DW-MRI provides best conspicuity of intrahepatic or hilar mass-forming cholangiocarcinomas than the other MRI sequences ( P < 0.001). The use of normalized ADC using the liver as reference organ results in the most restricted distribution of ADC values of intrahepatic or hilar mass-forming cholangiocarcinomas (variation coefficient = 16.6%). Abstract: Objective: To qualitatively and quantitatively analyze the presentation of intrahepatic and hilar mass-forming cholangiocarcinoma with diffusion-weighted magnetic resonance imaging (DW-MRI). Materials and methods: Twenty-eight patients with histopathologically proven mass-forming cholangiocarcinoma (hilar, n = 17; intrahepatic, n = 11) underwent hepatic DW-MRI at 1.5-T using free-breathing acquisition and three b -values (0, 400, 800 s/mm 2 ). Cholangiocarcinomas were evaluated qualitatively using visual analysis of DW-MR images and quantitatively with conventional ADC and normalized ADC measurements using liver and spleen as reference organs. Results: All cholangiocarcinomas (28/28; 100%) were visible on DW-MR images. DW-MRI yielded best conspicuity of cholangiocarcinomas than the other MRI sequences ( P < 0.001). Seven cholangiocarcinomas (7/11; 64%) showed hypointense central area on DW-MR images. Conventional ADC value of cholangiocarcinomas (1.042 × 10 −3 mm 2 /s ± 0.221 × 10 −3 mm 2 /s; range: 0.616 × 10 −3 mm 2 /s to 2.050 × 10 −3 mm 2 /s) was significantly lower than that of apparently normal hepatic parenchyma (1.362 × 10 −3 mm 2 /s ± 0.187 × 10 −3 mm 2 /s) ( P < 0.0001), although substantial overlap was found. No significant differences in ADC and normalized ADC values were found between intrahepatic and hilar cholangiocarcinomas. The use of normalized ADC using the liver as reference organ resulted in the most restricted distribution of ADC values of cholangiocarcinomas (variation coefficient = 16.6%). Conclusion: There is a trend towards a common appearance of intrahepatic and hilar mass-forming cholangiocarcinomas on DW-MRI but variations may be observed. Familiarity with these variations may improve the diagnosis of mass-forming cholangiocarcinoma.